1953
DOI: 10.1039/tf9534901425
|View full text |Cite
|
Sign up to set email alerts
|

The chemical effects of pressure. Part 1

Abstract: Rate constants between 1 and 3000 atm have been measured for the unimolecular solvolyses of tert.-butyl chloride and benzotrichloride. They show that the effects of pressure on the velocities of liquid phase ionic reactions can be explained in terms of the solvation forces involved. Stearn and Eyring's theory of the influence of pressure is shown to be inadequate.The basic ionization constants of ammonia and methylamine have been measured at 1, 10o0, 2000 and 3000 atm. They confirm the suggestion that an incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

1959
1959
2010
2010

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(31 citation statements)
references
References 2 publications
0
31
0
Order By: Relevance
“…These effects are thermodynamically related to the decrease in the total volume that accompanies ionization reactions [23]. The experimental evidence for this increase is reported in the literature [3,4,10,12,29]. In particular Hamman [3] reported a critical compilation of the effects of pressure on ionization equilibria and of volume changes for the ionization of weak electrolyte.…”
Section: Conductance Measurementsmentioning
confidence: 95%
See 2 more Smart Citations
“…These effects are thermodynamically related to the decrease in the total volume that accompanies ionization reactions [23]. The experimental evidence for this increase is reported in the literature [3,4,10,12,29]. In particular Hamman [3] reported a critical compilation of the effects of pressure on ionization equilibria and of volume changes for the ionization of weak electrolyte.…”
Section: Conductance Measurementsmentioning
confidence: 95%
“…However, the design suffered from the misalignment of the two electrodes at high pressures and the cell constant was found to change [3]. At a similar time Buchanan and Hamann [10] constructed a glass cell in which pressure was transmitted by liquid mercury. The cell was immersed in insulating oil inside a high-tensile steel pressure vessel in a thermostat tank: the oil transmitted pressure from a separate commercial hand pump and was sealed in the vessel.…”
Section: Conductivity Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous work (1,2,3,4) has shown that for a number of reactions in aqueous solution the effects of pressure may be interpreted in terms of the electrostriction of the solvent around ions and dipoles. The present investigation consists of a study of reactions i~lvolving the attack by a hydroxide ion on large organic dye molecules.…”
Section: Introductionmentioning
confidence: 99%
“…Studies of a variety of reactions (Buchanan and Hamann, 1955) had lead to the conclusion that for reactions in which ions or fairly strong dipoles are concerned, the solvent effects are generally more important than the structural ones. If the electric field is weakened (Laidler, 1965) when the activated complex is formed (as where two bodies of opposite signs come together), there will be some release of bond solvent molecules and the volumes and entropies of activation will be positive.…”
Section: Comparison Of the Values Of Ea For The Mineral Fractions Indmentioning
confidence: 99%